Adaptation Options for Rice-Based Cropping Systems in Climate Risk-Prone Provinces in the Ca Mau Peninsula: An Assessment Report - Bui, Ba Bong; Nguyen, Van Bo; Le, Thanh Tung; Nguyen, Dinh Vuong; Chau, Tai Tao; Duong, Minh Tuan; Nguyen, Duc Trung (2019)
The assessment report focuses on the options for risk reductions, crop production, conversion, management and practices among the rice-based cropping systems in the provinces of Ca Mau Peninsula. The report also looks into the various issues affecting the agricultural transformation of the coastal provinces, such as: failure to recognize risks brought about by climate change; unpredictable prices of agricultural products in the local and world market; lack of linkages between farmers and potential markets; lack of knowledge and skills in growing new crops under the climate change; spontaneous breaching of provincial government plans in changing cropping systems; and lack of investments in modernizing agricultural infrastructure, among others.